Lipids and carotenoids may influence the neuropathology of Alzheimer's disease: A meta-analysis - Aman Tiwari; Avtar Singh Gautam; Ekta Swarnamayee Panda; Rakesh Kumar Singh (Archives of Gerontology and Geriatrics Plus)
Introduction: Various studies have supported the key role of altered levels of lipids and carotenoids in the pathogenesis of Alzheimer's disease (AD), as they have the potential to maintain neuronal and tissue homeostasis. Methods: We conducted literature search on the PubMed and Google Scholar databases from the inception until December 2023. Two independent authors (AT and ASG) performed the data extraction, study selection, and quality assessment. The review outcomes were the level of lipids and carotenoids in cerebrospinal fluid (CSF) and peripheral fluids (serum and plasma) of patients with AD. The Cochrane Collaboration's Review Manager 5.4 was used to conduct this meta-analysis. Results: 107 studies showing levels of lipids and carotenoids in CSF and peripheral fluid of participants were included for the analysis. Peripheral cholesterol (p = 0.04) and CSF cholesterol (p = 0.04), CSF 24S-hydroxycholesterol (p = 0.01), CSF 27-hydroxycholesterol (p = 0.005), peripheral low-density lipoprotein (p = 0.02), and peripheral triglyceride (p = 0.03) from the lipid category were found to be associated with AD patients. However, the levels of carotenoids like α-carotene (p = 0.0006), β-carotene (p < 0.0001), β-cryptoxanthin (p = 0.0001), lutein (p < 0.0001), lycopene (p < 0.0001), and zeaxanthin (p < 0.0001) were decreased in AD patients compared to control. Conclusion: We concluded that the level of lipids and carotenoids are clearly associated with AD pathology. These altered level of lipids and carotenoids may provide an insight into the early diagnosis of the disease.